EVALUASI PELAKSANAAN STANDAR PELAYANAN FARMASI DI RUMAH SAKIT UMUM DAERAH KELAS C DI PROPINSI NUSA TENGGARA BARAT - , M. Sidrotullah, Prof. Dr. Lukman Hakim, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Pharmacy as a place for a main and professional service in hospital has the important role for supporting quality health services. One attempt to improve the quality of pharmaceutical care was by implementing the standards of hospital pharmaceutical care. The research aimed at finding out illustration of the implementation of pharmaceutical care standard at Local Public Hospitals Class C in Nusa Tenggara Barat province, as well as supporting or obstacle factors in the implementation. This research was a descriptive study. The study was conducted in three local public hospitals class C in Nusa Tenggara Barat province. Data was collected by using interview method of pharmacy hospital service standard. This interview comprises seven standards that are divided in twenty three parameters. The Pharmacy Department is agree with standard if the percentage of mean score was more than 75%, the other way it is not agree with standard if the percentage of mean score was less than 75%. The research result showed that the implementation of pharmaceutical care standard at Local Public Hospitals Class C in Nusa Tenggara Barat province had not implemented well yet, which could be seen from the result showing the percentage of standard achievement of three hospitals were less than 75 %. The percentage of standard achievement of hospital A was 52, 12 %, hospital B was 54, 78 %, and hospital C was 44, 35 %. According to the interview, it was found out that the obstacles of the implementation of the care standard of pharmacy were not optimally hospital management support toward pharmacy care conducted, the insufficient means and infrastructure supplying supporting pharmacy care, the less number of pharmacist, ineffective pharmacy careâs documentation system, and the less continually evaluation in improving the implementation of pharmacy careâs work.